2018
DOI: 10.1186/s12886-018-0899-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of low vision and blindness among patients attending St. Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia

Abstract: BackgroundLow vision and blindness are major public health problems. A vast burden of worlds visually impaired live in low-income settings especially in sub Saharan Africa. In such settings the blindness is associated with considerable disability and excess mortality, resulting in huge economic and social consequence. The main purpose of this study was to determine the prevalence and associated factors of low vision and blindness among patients at St. Paul’s hospital millenium medical college.MethodsInstitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 18 publications
3
43
4
Order By: Relevance
“…Previous studies conducted globally and in different European and African countries including Ethiopia showed that being older age [ 12 22 ], rural residency [ 16 , 23 ], lower educational status [ 14 16 , 23 , 24 ], low monthly income [ 15 , 16 , 23 , 25 ], cataract [ 4 , 12 , 13 , 20 22 , 24 , 26 ], glaucoma [ 4 , 13 , 21 , 22 , 26 ], macular degeneration [ 4 – 6 , 17 , 22 , 26 – 28 ], chronic comorbid illnesses [ 12 , 15 , 20 , 26 , 29 31 ] and smoking [ 15 , 32 ] were factors associated with unilateral or bilateral visual impairment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies conducted globally and in different European and African countries including Ethiopia showed that being older age [ 12 22 ], rural residency [ 16 , 23 ], lower educational status [ 14 16 , 23 , 24 ], low monthly income [ 15 , 16 , 23 , 25 ], cataract [ 4 , 12 , 13 , 20 22 , 24 , 26 ], glaucoma [ 4 , 13 , 21 , 22 , 26 ], macular degeneration [ 4 – 6 , 17 , 22 , 26 – 28 ], chronic comorbid illnesses [ 12 , 15 , 20 , 26 , 29 31 ] and smoking [ 15 , 32 ] were factors associated with unilateral or bilateral visual impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies conducted in Ethiopia were focused on childhood visual impairment giving less attention to adulthood visual impairment [ 35 , 36 ], some studies were conducted as retrospective chart review which lacks some variables like family history of eye disease, history of eye trauma, chronic co morbidity and life style factors [ 21 , 22 ] and others were community surveys that are outdated and lacks clinical variables of visual impairment [ 5 ]. In Ethiopia, there are also newly emerging factors of visual impairment associated with chronic diseases and advancement in age.…”
Section: Introductionmentioning
confidence: 99%
“…Visual impairment is more prevalent in low and middle-income countries (LMICs), about 80-90% of the world's visually impaired people live in LMICs [7]. In Sub-Saharan African countries, about 70 million people had been reported to live with visual impairment and Ethiopia is believed to have one of the world's highest rates of blindness and low vision, of which about 80% is preventable or treatable [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The good news is that more than two third of this visual impairment and blindness can be avoidable either by prevention and treatment. According to 'vision 2020 the right to sight' plan, in 2020 preventable and avoidable causes of visual impairment and blindness will be reduced significantly to less than 0.5% in all countries or less than 1% in any community worldwide (18,19).…”
Section: Introductionmentioning
confidence: 99%